Recent Advances in the Treatment of Sickle Cell Disease - Salinas Cisneros, Gabriel; Thein, Swee L. (Frontiers in Physiology, 2020)
In the 100 years since sickle cell anemia (SCA) was first described in the medical literature, studies of its molecular and pathophysiological basis have been at the vanguard of scientific discovery. By contrast, the translation of such knowledge into developing treatments has been disproportionately slow and elusive. Recent years, however, have seen major advances on several fronts. A more detailed understanding of the switch from fetal to adult hemoglobin and the identification of epigenetic regulators such as histone deacetylase and DNA Methyltransferase 1, and -globin gene repressors (BCL11A and LRF) have been explored as possible therapeutic options. An unprecedented number of new drugs aimed at both the treatment and prevention of end-organ damage are now in the pipeline, outcomes from potentially curative treatments such as allogeneic hematopoietic stem cell transplantation are improving, and great strides are being made in gene therapy, where methods employing both anti-sickling β -globin lentiviral vectors and gene editing are now entering clinical trials. Encouragingly, after a century of neglect, the therapeutic landscape for SCD is improving.